Study on Designing and Manufacturing the Freeze Drying System with the Process of Freezing Moist Materials inside the Freeze Drying Chamber to Preserve Valuable Products - Nguyen, Tan Dzung; Chau, Thanh Tuan; Do, Thuy Khanh Linh (Journal of Technical Education Science, 2022)
Freeze drying is one of the most advanced drying technologies for food processing and preserving using temperature under 0oC or under the freezing point, and pressure of drying chamber environment under 4.58mmHg to process foods. This method helps to maintain the initial quality of proteins, lipids, carbohydrates, vitamins, bioactive substances and sensory activities… In this study, the calculation and design were carried out to find suitable technology parameters to make the freeze drying system in which the freezing process occurred inside the freeze drying chamber. Heat was transferred by short wavelength thermal radiation, l = 50´10-3 m. As a result, time of freeze drying had been shortened to 13.33h/batch. The system was successfully manufactured, showed the steadily working, producing the high quality products, and reduced products price. In the conditions of Vietnam, the freeze drying system replacing that of other countries is the indispensable factor to apply for processing and preserving foods.